The Impact of Sports and Health Physical Education Learning on Body Mass Index and Physical Fitness Before and During the Covid-19 Pandemic at SMP Negeri 1 Losari Cirebon - Ibnu Riyadi; Setya Rahayu; Sri Sumartiningsih (JUARA : Jurnal Olahraga, 2023)
This exercise aims to discover the Impact of Physical Education, Learning Sports, and Health on Body Mass Index and Physical Fitness Before and During the Covid 19 Pandemic at SMP Negeri 1 Losari Cirebon. Comparative research design with a research sample of 120 students. The sample in the study was taken by total sampling. The test instrument for measuring body mass index is measuring body weight with a kilogram scale and height with a meter in cm. Meanwhile, physical fitness is measured by the bleep test. The results of the study showed (1) There was an impact of learning sports and health physical education on body mass index before the covid 19 pandemic at SMP Negeri 1 Losari Cirebon (2) There was an impact of learning physical education sports and health on physical fitness before the covid 19 pandemic at SMP Negeri 1 Losari Cirebon.